Development and Characterization of a Biodegradable pH Indicator Film Using Plant-Based Pigments - Perera , Hasith; Hosan, Shen; Wijesekara, Dasith; Vithanage, Vimukthi; Koswattage, Kaveenga Rasika (Three E Science Institute, 2025)
Natural pigments derived from plants present a promising alternative to synthetic dyes for use as pH indicators, owing to their sustainable nature and minimal environmental impact. This study investigates the extraction and characterization of plant-based pigments to create pH-sensitive paper materials. Unlike synthetic pH indicators, which contribute to chemical waste and environmental pollution, these biodegradable alternatives offer an eco-friendly solution for pH testing. The work outlines a systematic approach to evaluate the color changes of plant pigments when exposed to various pH levels while simultaneously developing biological pH-dependent papers and assessing their potential applications as chemical sensing devices. Pigments were extracted from the flowers of Cosmos bipinnatus, Impatiens balsamina, Tabernaemontana divaricata, and Tagetes erecta. The paper substrates were composed of fibers from Panicum virgatum (switchgrass). Color transitions were analyzed using pH meter calibration and UV-visible spectroscopic techniques. Results indicated that the floral pigments in Impatiens balsamina exhibited significant color variation with pH due to anthocyanin content, while the pigments from Tagetes erecta demonstrated stability attributed to carotenoids. The resulting paper displayed strong pH sensitivity, confirming its viability as a pH detection tool. The findings support the potential of plant-based pigments for developing responsive pH paper. Future work should focus on enhancing pigment longevity, scaling production, and exploring practical applications in environmental monitoring, food preservation, and medical diagnostics.